Quality of urban green spaces influences residents' use of these spaces, physical activity, and overweight/obesity. (15th February 2021) - Knobel, Pablo; Maneja, Roser; Bartoll, Xavier; Alonso, Lucia; Bauwelinck, Mariska; Valentin, Antonia; Zijlema, Wilma; Borrell, Carme; Nieuwenhuijsen, Mark; Dadvand, Payam
Abstract: The quality characteristics of urban green spaces (UGS) have been suggested to play a critical role in their use and their potentials to exert health effects. However, epidemiological studies evaluating such a role are scarce. These studies have generally focused on a limited number of quality dimensions. We studied the association between 10 UGS quality dimensions, assessed through a comprehensive multidimensional tool, and physical activity, overweight/obesity, and UGS use. Our study was based on 2053 adults participating in the Barcelona Health Survey (2016) and the quality of 149 UGS located in Barcelona, Spain. For each participant, we abstracted the average and maximum quality score separately for each of the 10 quality dimensions and an overall quality score for the UGS within 300 m of the participant's residential address. Data on the study outcomes were obtained through face-to-face interviews. We developed logistic regression and negative binomial models to assess our evaluated associations and conducted mediation analyses between the different outcomes. We observed that the overall quality of UGS was associated with higher likelihood of engaging in moderate-to-vigorous physical activity (OR:1.13; 95% CI:1.00–1.27), lower risk of overweight/obesity (OR: 0.88; 95% CI: 0.79–0.98), and increased use of UGS (exponentiated regression coefficient: 1.08; 95% CI:1.01–1.15). For the quality dimensions, we observed different patterns of associations depending on the outcome; however, bird biodiversity and amenities seem to be relevant to all of our evaluated outcomes. The mediation analysis suggested that UGS use mediate the association between quality and physical activity, while physical activity mediates the association between quality and overweight/obesity. The novel results from this study will allow decision-makers better design UGS and directly pinpoint relevant quality dimensions to promote physical activity, reduce the risk of overweight/obesity and boost the use of UGS amongst citizens. Graphical abstract: Image 1 Highlights: Urban green quality influences physical activity, overweight and urban green use. Each quality dimension has different associations with the outcomes. Bird biodiversity and overall quality influence all outcomes.